Defect Analysis & Solution through Revolutionizing Recycled Paper Production: Analisis & Solusi Cacat melalui revolusi Produksi Kertas Daur Ulang - Rais, Sofyan Alim; Cahyana , Atikha Sidhi (Indonesian Journal of Innovation Studies, 2024)
This study investigates the root causes of defects in recycled paper production, focusing on GSM-related issues, and proposes solutions to mitigate these defects. Through a six-month data collection process involving observation, on-site inspections, surveys, and expert interviews, the research employs Failure Mode and Effect Analysis (FMEA) and Fault Tree Analysis (FTA) methodologies to identify key factors contributing to defects. Results reveal seven types of defects, with GSM defects being most prominent, attributed to factors such as insufficient training and inadequate supervision. Proposed improvements include enhanced training, raw material inspections, and improved monitoring practices. These findings offer valuable insights for the paper production industry, suggesting practical interventions to enhance product quality and production efficiency. Further research could explore additional methodologies such as Root Cause Analysis (RCA) or Six Sigma for continuous quality improvement. Highlights: 1. Thorough analysis: FMEA and FTA methodologies for defect root cause identification.2. Recommended solutions: Enhanced training and monitoring for quality improvement.3. Industry insights: Practical strategies to enhance production efficiency and product quality. Keywords: Recycled paper production, Defects, Root cause analysis, Improvement strategies, Quality enhancement